Application of artificial intelligence strategies to the analysis of neurotransmitter receptor dynamics in living cells - Delmont, Ignacio (2020)
Fil: Delmont, Ignacio. Pontificia Universidad Católica Argentina. Facultad de Ciencias Médicas. Instituto de Investigaciones Biomédicas. Laboratorio de Biología Celular y Molecular; Argentina